Suffixation in Zhangzhou - Huang Yishan (Open Linguistics, 2024)
This study is the first to comprehensively describe suffixing morphology in Zhangzhou Southern Min, an under-described Sinitic language spoken in southern China. Suffixation can be derivational in this language to create new lexemes and expand local vocabulary but can be inflectional to convey grammatical information. It can also induce special tone sandhi patterns on either the lexical bases or the suffix itself. The bases that can undergo suffixation are cross-categorical, ranging from nouns, verbs, adjectives, classifiers, noun phrases, verb phrases to adjective phrases. However, the occurrences of suffixes, lexical bases, and derived items are subject to severe constraints from diverse factors of semantics, word class, syntax, phonology, and pragmatics. These reflect that the suffixing is not an isolated morphological event but rather involves systematic and complex interfaces among different linguistic levels. This study is a breakthrough to fill the research gap, while substantially broadening and deepening our knowledge of suffixation as an important morphological device in Sinitic languages. The study also contributes well-attested empirical data to the typology of suffixation in the world’s natural languages while shedding important light on how Sinitic languages and other so-called isolating languages should be better defined from a modern linguistic perspective.